2003
DOI: 10.1080/1388020039051741
|View full text |Cite
|
Sign up to set email alerts
|

New Anticancer Drugs from Cultured and Collected Marine Organisms

Abstract: This paper provides an outline of a collaborative research project

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…These results give new insights into the presence of molecular machineries for the production of naringenin chalcone or resveratrol, or, at least, what their homologs do in land plants. Marine microalgae possessing type I and II PKS enzymes are already known to produce polyketides with applications in human health and biotechnology [117][118][119][120]. We demonstrated that several lineages of microalgae possess type III PKS resembling CHS/STS genes, which posed new questions on their possible functions in microalgae.…”
Section: Discussionmentioning
confidence: 90%
“…These results give new insights into the presence of molecular machineries for the production of naringenin chalcone or resveratrol, or, at least, what their homologs do in land plants. Marine microalgae possessing type I and II PKS enzymes are already known to produce polyketides with applications in human health and biotechnology [117][118][119][120]. We demonstrated that several lineages of microalgae possess type III PKS resembling CHS/STS genes, which posed new questions on their possible functions in microalgae.…”
Section: Discussionmentioning
confidence: 90%
“…Many algae produce sulfated polysaccharides with antioxidant, antiviral and immunostimulatory activity (Huheihel et al, 2002;Lee et al, 2006;Pugh et al, 2001;Tannin-Spitz et al, 2005;Yim et al, 2004), vitamin E (Carballo-Cardenas et al, 2003, carotenoids and other pigments with anticancer and antioxidant effects (Ebermann et al, 1996;Moreau et al, 2006) and various toxins exhibiting cytotoxic, antiviral, antibacterial and antifungal activities. Several large screening programs of bioprospecting with algal extracts have been performed or are ongoing to identify bioactive compounds of medical significance (Døskeland, 2001;Fenical et al, 2003;Gerwick et al, 1994;Scholz and Liebezeit, 2006;Ö rdög et al, 2004). As discussed below, most of these important substances are secondary metabolites, and the possibility of combinatorial biosynthesis for heterologous expression of their genes have been reviewed (Julsing et al, 2006).…”
Section: Module 4 -Extraction Of Health Promoting Biomoleculesmentioning
confidence: 98%
“…These grants involved both academia and the pharmaceutical industry, with in this case, NIH/NCI involvement. The NCDDG consortium that discovered halimide (68) was led by the Fenical group at the Scripps Oceanographic Institution in La Jolla California, with a report covering their initial results published in 2000 [56]. Fenical and Jensen set up the small company Nereus to further develop agents from the NCDDG and other microbial sources.…”
Section: Plinabulin Clinical Trialsmentioning
confidence: 99%